MOLECULAR CHARACTERIZATION OF LACTOBACILLUS FROM BROILER AND IN-VITRO DETOXIFICATION OF AFLATOXIN B1 - R. Yasmeen 1; A. S. Hashmi; M. Athar; M. Tayyab 4and A. A. Anjum (Journal of Animal and Plant Sciences, 2021)
Aflatoxin B1 (AFB1) is the most hazardous toxin in food and feed components. Lactobacilli are extensively studied probiotic bacteria with detoxification characteristics. This study was conducted to isolate Lactobacillus from broiler gut, identify them by 16S ribosomal RNA (16S r RNA) gene sequence and evaluate their detoxification ability against AFB1. A total of fourteen Lactobacillus isolates were obtained from poultry gut and were identified. Phylogenetic study on the base of 16S rRNA gene showed that isolates from same species and source are genetically close to each other as compared to other isolates. Out of fourteen isolates, five have shown detoxification ability against AFB1 (50 ppb), in aqueous environment at 37 °C for 6 hours. Viable cells and cell walls have removed more concentration of AFB1 as compared to cell metabolites. Isolate Cr. 4 (L. salivarius) removed the highest amount (92.3%) of AFB1 as compared to other isolates. It was concluded that Lactobacillus isolates from broiler gut are potentially active detoxifying agents against AFB1 and their detoxification ability is strain dependent.
Keywords: Lactobacillus; Aflatoxin B1; detoxification; in vitro